Dampak program perhutanan sosial terhadap pertumbuhan usaha dan deforestasi: bukti empiris dari Indonesia - Mulyana Mulyana; Jossy Pranata Moeis (e-Jurnal Ekonomi Sumberdaya dan Lingkungan, 2022)
Since 2015 the Government of Indonesia has targeted ​​12.7 hectares land reform through the social forestry program (SFP).This paper traces village SFP beneficiaries and compares them to villages that have forests that did not receive SFP on the three islands of Sumatra, Kalimantan and Sulawesi in Indonesia. The empirical analysis used the Instrumental variable method and in-depth interviews. The findings of this study indicate that the existence of SFPs has not had a significant impact on the growth in the number of businesses and deforestation in both protected and production forests zone. The reason due to limited land due to restrictions on post-determination of social forests, the entrepreneurial capacity of forest managers, not yet integrated SFP with village programs, and low capital and utilization of forest product processing technology. Meanwhile, SFPhas not yet had an impact on deforestation because of the low quality of forest management planning and policy interventions related to forest planting in critical land that hasn’tbeen optimal yet.